A self-supporting flame-retardant polymer electrolyte and a preparation method and application thereof, and a solid-state lithium metal battery
By preparing a self-supporting flame-retardant polymer electrolyte, the safety hazards and combustion risks of lithium metal batteries are solved, and good cycle stability and safety under high voltage are achieved. The electrolyte skeleton formed by polymerization of acrylonitrile, phosphate ester and crosslinking agent has dual flame-retardant effect and is suitable for solid-state lithium metal batteries.
Patent Information
- Application Number
- CN202510559898.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2025-11-21
- Estimated Expiration
- 2045-04-29
AI Technical Summary
Existing lithium metal batteries use organic liquid electrolytes, which pose safety hazards. They are flammable and can easily cause lithium dendrites to pierce the separator, leading to short circuits, fires, or even explosions. Furthermore, the commonly used polymer matrix does not have self-extinguishing properties after contact with open flames, resulting in a high risk of combustion.
A self-supporting flame-retardant polymer electrolyte is prepared by polymerizing nitriles, phosphate esters containing unsaturated carbon-carbon double bonds, and crosslinking agents to form a crosslinked polymer skeleton, and dispersing succinic acid, triethyl phosphate, and lithium salt in the skeleton. The polymerization is initiated by light radiation, thus preparing an electrolyte with dual flame-retardant effects.
It achieves self-extinguishing without continuous combustion after contact with an open flame, has excellent high voltage resistance and a good electrochemical window, and significantly improves the cycle stability and safety of lithium metal batteries. The high-voltage Li||NCM811 battery retains 90% of its capacity after 100 cycles.
Smart Images

Figure CN120221780B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid-state lithium metal battery technology, specifically relating to a self-supporting flame-retardant polymer electrolyte, its preparation method and application, and solid-state lithium metal batteries. Background Technology
[0002] In recent years, with the gradual development of electric vehicles (EVs), lithium metal batteries have received widespread attention. Unlike traditional lithium-ion batteries, lithium metal batteries (LMBs) use lithium metal instead of graphite as the anode. Lithium metal has a high theoretical specific capacity (3860 mAh·g). -1 The lower electrochemical negative potential (relative to the standard hydrogen electrode of -3.04V) results in higher energy density (over 300 Wh / kg). Frustratingly, safety issues with traditional organic liquid electrolytes limit the further development of lithium metal batteries. Violent side reactions between the electrolyte and metallic lithium can lead to lithium dendrite formation. If these dendrites puncture the separator, the battery faces the risk of short circuits, fires, and even explosions. Furthermore, the high flammability of the small organic molecules in the electrolyte significantly increases the battery's safety hazards.
[0003] To address the current challenges of liquid lithium metal batteries, solid-state lithium metal batteries have emerged. By replacing traditional electrolytes with leak-free and high-energy-density solid-state electrolytes (SSEs), the safety and energy density of lithium metal batteries are significantly improved. Among solid-state electrolytes, solid polymer electrolytes (SPEs) are considered promising candidates for large-scale industrialization due to their excellent mechanical properties and ease of processing. However, currently commonly used polymer matrices (such as polyethylene oxide (PEO)) do not possess self-extinguishing capabilities upon contact with open flames and still pose a risk of combustion. Summary of the Invention
[0004] In view of this, the purpose of this invention is to provide a self-supporting flame-retardant polymer electrolyte, its preparation method and application, and a solid-state lithium metal battery. The self-supporting flame-retardant polymer electrolyte of this invention has good flame retardancy.
[0005] The present invention provides a self-supporting flame-retardant polymer electrolyte comprising a cross-linked polymer backbone formed by polymerization of an acrylonitrile, a phosphate ester containing unsaturated carbon-carbon double bonds and a cross-linking agent, and succinic anionibacterium, triethyl phosphate and lithium salt dispersed in the cross-linked polymer backbone.
[0006] Preferably, the phosphate ester containing unsaturated carbon-carbon double bonds includes one or more of dimethyl vinylphosphonate, diethyl vinylphosphonate, vinylphosphonic acid, and dimethyl allyl phosphate.
[0007] Preferably, the mass ratio of the acrylonitrile to the phosphate ester containing unsaturated carbon-carbon double bonds is (0.1-2):1.
[0008] Preferably, the mass ratio of the succinic anion and the phosphate ester containing unsaturated carbon-carbon double bonds is (0.1-6):2.
[0009] Preferably, the mass ratio of triethyl phosphate to succinic acid is (0.1-2):5.
[0010] Preferably, the lithium salt includes one or more of lithium perchlorate, lithium hexafluorophosphate, lithium nitrate, lithium difluorooxalate borate, lithium trifluoromethanesulfonate, lithium bis(difluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium fluoride, and lithium difluorophosphate, and the mass ratio of the lithium salt to succinic acid is (0.1-2):1.
[0011] Preferably, the crosslinking agent includes one or more of ethoxylated trimethylolpropane triacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, N,N-methylenebisacrylamide, triallyl isocyanate, and polyethylene glycol methyl ether methacrylate.
[0012] This invention also provides a method for preparing the self-supporting flame-retardant polymer electrolyte described in the above technical solution, comprising the following steps:
[0013] A mixture of nitrile compounds, phosphate esters containing unsaturated carbon-carbon double bonds, succinic acid, triethyl phosphate, lithium salt, crosslinking agent, and initiator is subjected to photo-radiation polymerization to obtain the self-supporting flame-retardant polymer electrolyte.
[0014] The present invention also provides the application of the self-supporting flame-retardant polymer electrolyte described in the above technical solution or the self-supporting flame-retardant polymer electrolyte obtained by the above preparation method in solid-state lithium metal batteries.
[0015] The present invention also provides a solid-state lithium metal battery, comprising a positive electrode material, a self-supporting flame-retardant polymer electrolyte, and a negative electrode material;
[0016] The self-supporting flame-retardant polymer electrolyte is the self-supporting flame-retardant polymer electrolyte described in the above technical solution or the self-supporting flame-retardant polymer electrolyte obtained by the above preparation method.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] The present invention provides a self-supporting flame-retardant polymer electrolyte comprising a cross-linked polymer backbone formed by polymerization of an acrylonitrile, a phosphate ester containing unsaturated carbon-carbon double bonds and a cross-linking agent, and succinic anionibacterium, triethyl phosphate and lithium salt dispersed in the cross-linked polymer backbone.
[0019] The self-supporting flame-retardant polymer electrolyte of this invention comprises an electrolyte polymer skeleton formed by the polymerization of olefinic substances with unsaturated double bonds and phosphate esters (unsaturated phosphate esters) containing unsaturated carbon-carbon double bonds. The olefinic substances contain nitrogen, and the unsaturated phosphate esters contain phosphorus. This invention introduces synergistically flame-retardant olefinic substances and unsaturated phosphate esters into the polymer skeleton, while simultaneously introducing non-flammable succinic anionyl and flame-retardant triethyl phosphate into the polymer skeleton, achieving a dual flame-retardant effect. It can rapidly self-extinguish upon contact with an open flame, without any sustained combustion, exhibiting excellent flame retardancy. Furthermore, the electrolyte raw materials of this invention include olefinic substances and succinic anionyl, containing cyano functional groups with ultra-high antioxidant properties. The resulting self-supporting flame-retardant polymer electrolyte exhibits excellent high-voltage performance, with an electrochemical window reaching 4.8V, and can be matched with high-nickel NCM811 cathodes. When applied to lithium metal batteries, the capacity retention rate of high-voltage Li||NCM811 batteries reaches 90% after 100 cycles, demonstrating good cycle stability.
[0020] The present invention also provides a method for preparing the self-supporting flame-retardant polymer electrolyte described in the above technical solution. The method involves initiating double bond polymerization through photoradiation, which is simple to operate, has abundant raw material sources, and is inexpensive, providing a new approach for the industrialization of high-safety polymer electrolytes. Attached Figure Description
[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0022] Figure 1 An optical photograph of the self-supporting flame-retardant polymer electrolyte prepared in Example 1;
[0023] Figure 2 SEM comparison images of the self-supporting flame-retardant polymer electrolyte membranes prepared in Examples 1, 2 and 3;
[0024] Figure 3 SEM image of the polymer electrolyte membrane prepared in Comparative Example 1;
[0025] Figure 4 LSV diagram of the self-supporting flame-retardant polymer electrolyte prepared in Example 2;
[0026] Figure 5 The self-supported flame-retardant polymer electrolyte prepared in Example 3, along with the lithium metal anode and LiNi 0.8 Co 0.1 Mn0.1 Cycling performance of a lithium battery with an O2 cathode assembly at 0.5C;
[0027] Figure 6 The self-supported flame-retardant polymer electrolyte prepared in Example 3, along with the lithium metal anode and LiNi 0.8 Co 0.1 Mn 0.1 Charge-discharge curves of a lithium battery assembled with an O2 cathode at 0.5C;
[0028] Figure 7 The flame retardant performance test results of the self-supporting electrolyte membranes prepared in Examples 1, 2, 3 and Comparative Example 1 are shown, where a is the electrolyte obtained in Example 1, b is the electrolyte obtained in Example 2, c is the electrolyte obtained in Example 3 and d is the electrolyte obtained in Comparative Example 1.
[0029] Figure 8 LSV diagram of the self-supporting electrolyte membrane prepared in Comparative Example 1;
[0030] Figure 9 The self-supporting electrolyte membrane prepared for Comparative Example 1 and the lithium metal anode and LiNi 0.8 Co 0.1 Mn 0.1 Cycling performance of lithium metal batteries assembled with O2 cathode at 0.5C;
[0031] Figure 10 The self-supporting electrolyte membrane prepared for Examples 1 and 4, and the lithium metal anode and LiNi 0.8 Co 0.1 Mn 0.1 Cycling performance of lithium metal batteries assembled with O2 cathode at 0.5C;
[0032] Figure 11 The self-supporting electrolyte membrane prepared for Examples 1 and 5 and the lithium metal anode and LiNi 0.8 Co 0.1 Mn 0.1 Cycling performance of lithium metal batteries assembled with O2 cathode at 0.5C;
[0033] Figure 12 The self-supporting electrolyte membranes prepared for Examples 1, 2, and 3, and the lithium metal anode and LiNi 0.8 Co 0.1 Mn 0.1 Cycling performance of a lithium metal battery assembled with an O2 cathode at 0.5C. Detailed Implementation
[0034] The present invention provides a self-supporting flame-retardant polymer electrolyte comprising a cross-linked polymer backbone formed by polymerization of an acrylonitrile, a phosphate ester containing unsaturated carbon-carbon double bonds and a cross-linking agent, and succinic anionibacterium, triethyl phosphate and lithium salt dispersed in the cross-linked polymer backbone.
[0035] Unless otherwise specified, all materials and equipment used in this invention are commercially available products in the field.
[0036] In this invention, the self-supporting flame-retardant polymer electrolyte is preferably a self-supporting membrane with a cross-linked structure, wherein acrylonitrile, phosphate ester containing unsaturated carbon-carbon double bonds, and cross-linking agent are polymerized through double bond polymerization to form a self-supporting cross-linked polymer skeleton, and succinic anion, triethyl phosphate, and lithium salt are dispersed in the skeleton.
[0037] In this invention, the acrylonitrile is preferably acrylonitrile. The acrylonitrile contains an antioxidant cyano functional group, which can provide excellent high voltage resistance for the polymer electrolyte. The acrylonitrile is polymerized with a phosphate ester containing unsaturated carbon-carbon double bonds to obtain a polymer skeleton containing N and P elements, which can play a synergistic flame retardant role.
[0038] In this invention, the phosphate ester containing unsaturated carbon-carbon double bonds preferably includes one or more of dimethyl vinylphosphonate, diethyl vinylphosphonate, vinylphosphonic acid, and dimethyl allyl phosphate.
[0039] In this invention, the preferred mass ratio of the nitrile material to the phosphate ester containing unsaturated carbon-carbon double bonds is (0.1–2):1, more preferably (0.1–1):1, and specifically 1:2 or 1:4. The nitrile material exhibits excellent oxidation resistance due to the presence of cyano groups, allowing it to withstand higher voltages. Therefore, when the content of the nitrile material is appropriately increased, the cycle stability of the battery will be better.
[0040] In this invention, the preferred mass ratio of succinic anionylene to the phosphate ester containing unsaturated carbon-carbon double bonds is (0.1–6):2, more preferably (3–5):2, and specifically 5:2 or 2:1. Increasing the succinic anionylene content helps improve the ionic conductivity of the electrolyte, thereby enhancing its lithium-ion transport capacity, which leads to an increase in the discharge specific capacity of the corresponding battery. Simultaneously, the cyano groups on the succinic anionylene also have antioxidant properties, providing excellent high-voltage resistance to the electrolyte, thus improving the cycle stability of the corresponding battery when matched with a high-voltage cathode.
[0041] In this invention, the preferred mass ratio of triethyl phosphate to succinic anion is (0.1–2):5, more preferably (0.1–1):5, and specifically 1:5. Triethyl phosphate can improve the ionic conductivity of the electrolyte to a certain extent, thereby increasing the discharge specific capacity of the battery. However, excessive triethyl phosphate will increase the viscosity of the system and cause side reactions with metallic lithium, resulting in a decrease in the discharge specific capacity of the battery. Simultaneously, the triethyl phosphate can improve the flame retardant effect.
[0042] In this invention, the lithium salt preferably includes one or more of lithium perchlorate, lithium hexafluorophosphate, lithium nitrate, lithium difluorooxalate borate, lithium trifluoromethanesulfonate, lithium bis(difluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium fluoride, and lithium difluorophosphate; the lithium salt provides lithium ions.
[0043] In this invention, the preferred mass ratio of lithium salt to succinic anion is (0.1–2):1, more preferably (0.1–1):1, and specifically 1:1. The lithium salt content described in this invention results in high ionic conductivity.
[0044] In this invention, the crosslinking agent preferably comprises one or more of ethoxylated trimethylolpropane triacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, N,N-methylenebisacrylamide, triallyl isocyanate, and polyethylene glycol methyl ether methacrylate. The crosslinking agent is used to promote the crosslinking reaction of unsaturated double bonds, forming a self-supporting backbone of the polymer electrolyte.
[0045] In this invention, the mass ratio of the crosslinking agent to the phosphate ester containing unsaturated carbon-carbon double bonds is preferably (1-3):2, more preferably (1-2):2, and specifically 1:1.
[0046] In this invention, the initiator preferably includes one or more of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexylphenyl ketone, 2-methyl-2-(4-morpholino)-1-[4-(methylthio)phenyl]-1-propanone, 1-hydroxycyclohexylbenzophenone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, benzophenone, 4-methylbenzophenone, and methyl benzoylformate; the initiator is used to initiate the crosslinking reaction of unsaturated double bonds in the raw materials.
[0047] In this invention, the preferred mass ratio of the initiator to the total mass of other raw materials in the preparation raw materials is (0.1-2):100, more preferably 0.02:1.5-1.6. The amount of initiator used in this invention will not result in low degree of polymerization and failure to form a film, nor will it result in high degree of polymerization and high impedance.
[0048] This invention also provides a method for preparing the self-supporting flame-retardant polymer electrolyte described in the above technical solution, comprising the following steps:
[0049] A self-supporting flame-retardant polymer electrolyte is obtained by mixing nitriles, phosphate esters containing unsaturated carbon-carbon double bonds, succinic acid, triethyl phosphate, lithium salt, crosslinking agent and initiator and then performing photo-radiation polymerization.
[0050] In this invention, the mixing of the nitrile substance, the phosphate ester containing unsaturated carbon-carbon double bonds, succinic acid, triethyl phosphate, lithium salt, crosslinking agent and initiator preferably includes: first mixing the nitrile substance, the phosphate ester containing unsaturated carbon-carbon double bonds, succinic acid, triethyl phosphate, lithium salt and crosslinking agent, and second mixing the resulting mixture with the initiator to obtain the precursor;
[0051] Both the first mixing and the second mixing are preferably carried out in an inert gas atmosphere, and both the first mixing and the second mixing are preferably carried out by stirring. The present invention does not have special requirements for the stirring speed and time.
[0052] In this invention, the process preferably includes, before photoradiation polymerization, pouring the obtained precursor into a mold. The photoradiation polymerization preferably uses a mercury lamp, with a light intensity preferably between 350W and 500W. The photoradiation polymerization time is preferably 1 to 10 minutes, more preferably 3 to 5 minutes. This invention initiates free radical crosslinking polymerization of unsaturated double bonds through photoradiation.
[0053] The present invention also provides the application of the self-supporting flame-retardant polymer electrolyte described in the above technical solution or the self-supporting flame-retardant polymer electrolyte obtained by the above preparation method in solid-state lithium metal batteries.
[0054] The present invention also provides a solid-state lithium metal battery, comprising a positive electrode material, a self-supporting flame-retardant polymer electrolyte, and a negative electrode material;
[0055] The self-supporting flame-retardant polymer electrolyte is the self-supporting flame-retardant polymer electrolyte described in the above technical solution or the self-supporting flame-retardant polymer electrolyte obtained by the above preparation method.
[0056] In this invention, the positive electrode material preferably includes lithium iron phosphate, lithium cobalt oxide, lithium nickel manganese oxide, or nickel cobalt manganese ternary material; the negative electrode material is preferably lithium metal.
[0057] The electrolyte of this invention is a self-supporting nitrogen-phosphorus synergistic flame-retardant polymer electrolyte, which exhibits high ionic conductivity, a wide electrochemical window, and good flame retardancy. Furthermore, the preparation method of this invention is simple and can save battery costs. When the flame-retardant polymer electrolyte is applied to lithium metal batteries, the capacity retention rate of a high-voltage Li||NCM811 battery can reach 90% after 100 cycles. In contrast, a polymer electrolyte without an NP backbone, used as a comparative example, has no flame-retardant effect, and the capacity retention rate of a high-voltage Li||NCM811 battery after 70 cycles is only 23.3%.
[0058] To further illustrate the present invention, the self-supporting flame-retardant polymer electrolyte, its preparation method and application, and solid-state lithium metal batteries provided by the present invention will be described in detail below with reference to the accompanying drawings and embodiments. However, these descriptions should not be construed as limiting the scope of protection of the present invention.
[0059] Example 1
[0060] 0.2g of trimethylolpropane trimethacrylate, 0.1g of acrylonitrile, 0.2g of dimethyl vinylphosphonate, 0.1g of triethyl phosphate, 0.5g of succinic anion, 0.5g of lithium bis(trifluoromethanesulfonyl)imide, and 0.02g of 2-hydroxy-2-methyl-1-phenylpropanone were mixed in an inert gas atmosphere and stirred at 300 rpm to obtain a homogeneous precursor. The precursor was poured onto a mold and irradiated with a 350W mercury lamp for 3 minutes to obtain a self-supporting flame-retardant polymer electrolyte membrane.
[0061] Example 2
[0062] 0.2g of trimethylolpropane trimethacrylate, 0.1g of acrylonitrile, 0.2g of diethyl vinylphosphonate, 0.1g of triethyl phosphate, 0.5g of succinic anion, 0.5g of lithium bis(trifluoromethanesulfonyl)imide, and 0.02g of 2-hydroxy-2-methyl-1-phenylpropanone were mixed in an inert gas atmosphere and stirred at 300 rpm to obtain a homogeneous precursor. The precursor was poured onto a mold and irradiated with a 350W mercury lamp for 3 minutes to obtain a self-supporting flame-retardant polymer electrolyte membrane.
[0063] Example 3
[0064] 0.2g of trimethylolpropane trimethacrylate, 0.1g of acrylonitrile, 0.2g of dimethyl allyl phosphate, 0.1g of triethyl phosphate, 0.5g of succinic anion, 0.5g of lithium bis(trifluoromethanesulfonyl)imide, and 0.02g of 2-hydroxy-2-methyl-1-phenylpropanone were mixed in an inert gas atmosphere and stirred at 300 rpm to obtain a homogeneous precursor. The precursor was poured onto a mold and irradiated with a 350W mercury lamp for 3 minutes to obtain a self-supporting flame-retardant polymer electrolyte membrane.
[0065] Comparative Example 1
[0066] 0.2 g of trimethylolpropane trimethacrylate, 0.5 g of succinate, 0.35 g of lithium bis(trifluoromethanesulfonyl)imide and 0.02 g of 2-hydroxy-2-methyl-1-phenylpropanone were mixed in an inert gas atmosphere and stirred at 300 r / min to obtain a homogeneous precursor. The precursor was poured onto a mold and irradiated with light using a 350 W mercury lamp for 3 min to obtain a self-supporting polymer electrolyte membrane.
[0067] Example 4
[0068] 0.2g of trimethylolpropane trimethacrylate, 0.05g of acrylonitrile, 0.2g of dimethyl vinylphosphonate, 0.1g of triethyl phosphate, 0.5g of succinic anion, 0.5g of lithium bis(trifluoromethanesulfonyl)imide, and 0.02g of 2-hydroxy-2-methyl-1-phenylpropanone were mixed in an inert gas atmosphere and stirred at 300 rpm to obtain a homogeneous precursor. The precursor was poured onto a mold and irradiated with a 350W mercury lamp for 3 minutes to obtain a self-supporting flame-retardant polymer electrolyte membrane.
[0069] Example 5
[0070] 0.2g of trimethylolpropane trimethacrylate, 0.1g of acrylonitrile, 0.2g of dimethyl vinylphosphonate, 0.1g of triethyl phosphate, 0.4g of succinic anion, 0.5g of lithium bis(trifluoromethanesulfonyl)imide, and 0.02g of 2-hydroxy-2-methyl-1-phenylpropanone were mixed in an inert gas atmosphere and stirred at 300 rpm to obtain a homogeneous precursor. The precursor was poured onto a mold and irradiated with a 350W mercury lamp for 3 minutes to obtain a self-supporting flame-retardant polymer electrolyte membrane.
[0071] Comparative Example 2
[0072] 0.2g of trimethylolpropane trimethacrylate, 0.1g of acrylonitrile, 0.2g of dimethyl vinylphosphonate, 0.2g of triethyl phosphate, 0.4g of succinic anion, 0.5g of lithium bis(trifluoromethanesulfonyl)imide, and 0.02g of 2-hydroxy-2-methyl-1-phenylpropanone were mixed in an inert gas atmosphere and stirred at 300 rpm to obtain a homogeneous precursor. The precursor was poured onto a mold and irradiated with a 350W mercury lamp for 3 minutes to obtain a self-supporting flame-retardant polymer electrolyte membrane.
[0073] Comparative Example 3
[0074] 0.2g of trimethylolpropane trimethacrylate, 0.1g of acrylonitrile, 0.2g of dimethyl vinylphosphonate, 0.4g of succinic acid, 0.5g of lithium bis(trifluoromethanesulfonyl)imide, and 0.02g of 2-hydroxy-2-methyl-1-phenylpropanone were mixed in an inert gas atmosphere and stirred at 300 rpm to obtain a homogeneous precursor. The precursor was poured onto a mold and irradiated with a 350W mercury lamp for 3 minutes to obtain a self-supporting flame-retardant polymer electrolyte membrane.
[0075] Morphological characteristics
[0076] (1) Figure 1 An optical photograph of the self-supporting flame-retardant polymer electrolyte membrane prepared in Example 1.
[0077] Depend on Figure 1 It is known that the self-supporting flame-retardant polymer electrolyte membrane prepared by the present invention is a colorless and transparent self-supporting membrane.
[0078] (2) Figure 2 SEM comparison images of the self-supporting flame-retardant polymer electrolyte membranes prepared in Examples 1, 2 and 3, where a is Example 1, b is Example 2 and c is Example 3.
[0079] Depend on Figure 2 It can be seen that the morphology of the electrolyte membrane microstructure cross-linked structure obtained in the three embodiments is different. The cross-linked structure in Example 1 tends to be in a consistent direction, while the cross-linked structures in Examples 2 and 3 are more like a fishing net. Among them, the structure of Example 3 has smaller and denser cross-linked domains than that of Example 2. The difference in cross-linked structure is attributed to the different structures of the phosphate esters containing unsaturated carbon-carbon double bonds in the three embodiments.
[0080] (3) Figure 3 SEM image of the polymer electrolyte membrane prepared for Comparative Example 1.
[0081] Depend on Figure 3 It can be seen that the electrolyte membrane obtained in Comparative Example 1 did not show any obvious cross-linking structure.
[0082] Performance testing
[0083] (1) Figure 4 The image shows the LSV diagram of the self-supporting flame-retardant polymer electrolyte membrane prepared in Example 2.
[0084] Depend on Figure 4 It can be seen that the electrochemical window of the self-supporting flame-retardant polymer electrolyte prepared by the present invention is 4.8V, and it has good antioxidant capacity.
[0085] (2) Figure 5 The self-supporting flame-retardant polymer electrolyte membrane prepared in Example 3, along with the lithium metal anode and LiNi0.8 Co 0.1 Mn 0.1 Cycling performance of a lithium metal battery assembled with an O2 cathode at 0.5C.
[0086] Depend on Figure 5 It can be seen that the self-supporting flame-retardant polymer electrolyte membrane prepared by this invention is compatible with lithium metal anodes and LiNi 0.8 Co 0.1 Mn 0.1 Lithium metal batteries assembled with O2 cathodes can achieve a maximum discharge specific capacity of 162.89 mAh·g at 0.5C. -1 After 100 cycles, the capacity retention rate is 90%.
[0087] (3) Figure 6 The self-supporting flame-retardant polymer electrolyte membrane prepared in Example 3, along with the lithium metal anode and LiNi 0.8 Co 0.1 Mn 0.1 The charge-discharge curves of a lithium metal battery assembled with an O2 cathode at 0.5C.
[0088] Depend on Figure 6 It can be seen that the self-supporting flame-retardant polymer electrolyte membrane prepared by this invention is compatible with lithium metal anodes and LiNi 0.8 Co 0.1 Mn 0.1 Lithium metal batteries assembled with O2 cathodes can achieve a coulombic efficiency of 98% at 0.5C. The high coulombic efficiency also indicates good reversibility.
[0089] (4) Figure 7 The flame retardant performance test results of the self-supporting electrolyte membranes prepared in Examples 1, 2, 3 and Comparative Example 1 are shown, where a is the electrolyte obtained in Example 1, b is the electrolyte obtained in Example 2, c is the electrolyte obtained in Example 3 and d is the electrolyte obtained in Comparative Example 1.
[0090] Depend on Figure 7 It can be seen that the self-supporting flame-retardant electrolytes of Examples 1, 2, and 3 did not exhibit open flame or combustion during continuous contact with a flame for up to 6 seconds, but instead produced self-extinguishing white smoke. In contrast, the self-supporting electrolyte membrane of Comparative Example 1 burned violently upon contact with a flame, and the entire electrolyte membrane decomposed after 6 seconds. The flame-retardant data from Comparative Example 1 shows that polymers containing only nitrogen have poor flame-retardant ability, melting upon contact with a flame and burning after more than 2 seconds. In contrast, the polymer backbone of Example 1 contains N and P, exhibiting synergistic flame-retardant properties and demonstrating good flame-retardant effect.
[0091] (5) Figure 8 The LSV diagram is for the self-supporting electrolyte membrane prepared in Comparative Example 1.
[0092] Depend on Figure 8 It can be seen that the electrochemical window of the self-supporting flame-retardant electrolyte prepared in Comparative Example 1 is 4.3V, which is weaker than the high voltage resistance of the self-supporting flame-retardant electrolyte membrane prepared in Example 2.
[0093] (6) Figure 9 The self-supporting electrolyte membrane prepared for Comparative Example 1 and the lithium metal anode and LiNi 0.8 Co 0.1 Mn 0.1 Cycling performance of a lithium metal battery assembled with an O2 cathode at 0.5C.
[0094] Depend on Figure 9 It can be seen that the self-supporting electrolyte membrane prepared in Comparative Example 1 is compatible with the lithium metal anode and LiNi 0.8 Co 0.1 Mn 0.1 The lithium metal battery assembled with an O2 cathode has a discharge specific capacity of 152 mAh·g at 0.5C. -1 During cycling, the battery capacity rapidly decreases, and the cycle stability is poor. After 70 cycles, the capacity retention rate of the high-voltage Li||NCM811 battery is only 23.3%.
[0095] (7) Figure 10 The self-supporting electrolyte membrane prepared for Examples 1 and 4, and the lithium metal anode and LiNi 0.8 Co 0.1 Mn 0.1 Cycling performance of a lithium metal battery assembled with an O2 cathode at 0.5C.
[0096] Depend on Figure 10 It can be seen that the self-supporting electrolyte membrane prepared in Example 4 is compatible with the lithium metal anode and LiNi 0.8 Co 0.1 Mn 0.1 The lithium metal battery assembled with the O2 cathode had a lower discharge specific capacity at 0.5C than that of Example 1, and when cycled to the 77th cycle, the capacity retention rate of the lithium metal battery corresponding to Example 4 was 89.5%, which was lower than the capacity retention rate of 92.3% of the lithium metal battery corresponding to Example 1.
[0097] (8) Figure 11 The self-supporting electrolyte membranes prepared for Examples 1 (SN 0.5g) and 5 (SN 0.4g) and the lithium metal anode and LiNi 0.8 Co 0.1 Mn 0.1 Cycling performance of a lithium metal battery assembled with an O2 cathode at 0.5C.
[0098] Depend on Figure 11 It can be seen that the self-supporting electrolyte membrane prepared in Example 5 is compatible with the lithium metal anode and LiNi 0.8Co 0.1 Mn 0.1 The lithium metal battery assembled with the O2 cathode had a lower discharge specific capacity at 0.5C than that of Example 1, and when cycled to the 86th cycle, the capacity retention rate of the lithium metal battery corresponding to Example 5 was 68.8%, which was lower than the capacity retention rate of 92.9% of the lithium metal battery corresponding to Example 1.
[0099] (9) Figure 12 The self-supporting electrolyte membranes prepared for Example 1 (0.1 g of triethyl phosphate TEP), Comparative Example 2 (0.2 g of TEP), and Comparative Example 3 (0 g of TEP) were compared with lithium metal anodes and LiNi 0.8 Co 0.1 Mn 0.1 Cycling performance of a lithium metal battery assembled with an O2 cathode at 0.5C.
[0100] Depend on Figure 12 It can be seen that the self-supporting electrolyte membrane prepared in Comparative Example 2 is compatible with the lithium metal anode and LiNi 0.8 Co 0.1 Mn 0.1 The lithium metal battery assembled with an O2 cathode achieved a maximum discharge specific capacity of 162.99 mAh g at 0.5C. -1 Comparative Example 3 shows the self-supporting electrolyte membrane prepared with lithium metal anode and LiNi 0.8 Co 0.1 Mn 0.1 The lithium metal battery assembled with an O2 cathode achieved a maximum discharge specific capacity of 154.85 mAh g at 0.5C. -1 All are lower than the self-supporting electrolyte membrane and lithium metal anode and LiNi prepared in Example 1. 0.8 Co 0.1 Mn 0.1 The lithium metal battery assembled with an O2 cathode achieved a maximum discharge specific capacity of 170.33 mAh g at 0.5C. -1 .
[0101] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, not all embodiments. People can obtain other embodiments based on the present invention without creative effort, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A self-supporting flame-retardant polymer electrolyte, characterized in that, It includes a cross-linked polymer backbone formed by polymerizing nitrile substances, phosphate esters containing unsaturated carbon-carbon double bonds and cross-linking agents, as well as succinic acid, triethyl phosphate and lithium salt dispersed in the cross-linked polymer backbone; The mass ratio of the nitrile substance to the phosphate ester containing unsaturated carbon-carbon double bonds is (0.1~2):1; The mass ratio of the succinic acid and the phosphate ester containing unsaturated carbon-carbon double bonds is (0.1~6):2; The mass ratio of triethyl phosphate to succinic acid is (0.1~2):
5.
2. The self-supporting flame-retardant polymer electrolyte according to claim 1, characterized in that, The phosphate ester containing unsaturated carbon-carbon double bonds includes one or more of dimethyl vinylphosphonate, diethyl vinylphosphonate, vinylphosphonic acid, and dimethyl allyl phosphate.
3. The self-supporting flame-retardant polymer electrolyte according to claim 1, characterized in that, The lithium salt includes one or more of lithium perchlorate, lithium hexafluorophosphate, lithium nitrate, lithium difluorooxalate borate, lithium trifluoromethanesulfonate, lithium bis(difluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium fluoride, and lithium difluorophosphate, and the mass ratio of the lithium salt to succinic acid is (0.1~2):
1.
4. The self-supporting flame-retardant polymer electrolyte according to claim 1, characterized in that, The crosslinking agent includes one or more of ethoxylated trimethylolpropane triacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, N,N-methylenebisacrylamide, triallyl isocyanate, and polyethylene glycol methyl ether methacrylate.
5. The method for preparing the self-supporting flame-retardant polymer electrolyte according to any one of claims 1 to 4, characterized in that, Includes the following steps: A mixture of nitrile compounds, phosphate esters containing unsaturated carbon-carbon double bonds, succinic acid, triethyl phosphate, lithium salt, crosslinking agent, and initiator is subjected to photo-radiation polymerization to obtain the self-supporting flame-retardant polymer electrolyte.
6. The application of the self-supporting flame-retardant polymer electrolyte according to any one of claims 1 to 4 or the self-supporting flame-retardant polymer electrolyte obtained by the preparation method according to claim 5 in solid-state lithium metal batteries.
7. A solid-state lithium metal battery, characterized in that, This includes positive electrode materials, self-supporting flame-retardant polymer electrolytes, and negative electrode materials; The self-supporting flame-retardant polymer electrolyte is the self-supporting flame-retardant polymer electrolyte as described in any one of claims 1 to 4. The polymer electrolyte or the self-supporting flame-retardant polymer electrolyte obtained by the preparation method described in claim 5.
Citation Information
Patent Citations
Gel-formable electrolyte composition and lithiumsecondary batteries manufactured using the same andPreparation process thereof
KR1020040099606A
Flame-resistant electrolyte compositions from phosphonate vinyl monomers, quasi-solid and solid-state electrolytes, and lithium batteries
US20220238916A1